Mental disorder and clinical care in people convicted of homicide: national clinical survey. Issue 7193 (8th May 1999) - Shaw, Jenny; Appleby, Louis; Amos, Tim; McDonnell, Ros; Harris, Catherine; McCann, Kerry; Kiernan, Katy; Davies, Sue; Bickley, Harriet; Parsons, Rebecca
Abstract: Objectives: To estimate the rate of mental disorder in those convicted of homicide and to examine the social and clinical characteristics of those with a history of contact with psychiatric services. Design: National clinical survey. Setting: England and Wales. Subjects: Eighteen month sample of people convicted of homicide. Main outcome measures: Offence related and clinical information collected from psychiatric court reports on people convicted of homicide. Detailed clinical data collected on those with a history of contact with psychiatric services. Results: 718 homicides were reported to the inquiry between April 1996 and November 1997. Of the 500 cases for whom psychiatric reports were retrieved, 220 (44%; 95% confidence interval 40% to 48%) had a lifetime history of mental disorder, while 71 (14%; 11% to 17%) had symptoms of mental illness at the time of the homicide. Of the total sample, 102 (14%; 12% to 17%) were confirmed to have been in contact with mental health services at some time, 58 (8%; 6% to 10%) in the year before the homicide. The commonest diagnosis was personality disorder (20 cases, 22%; 13% to 30%). Alcohol and drug misuse were also common. Only 15 subjects (18%; 10% to 26%) were receiving intensive community care, and 60 (63%; 53% to 73%) were out of contact at the time of the homicide. Conclusions: There are substantial rates of mental disorder in people convicted of homicide. Most do not have severe mental illness or a history of contact with mental health services. Inquiry findings suggest that preventing loss of contact with services and improving the clinical management of patients with both mental illness and substance misuse may reduce risk, but clinical trials are needed to examine the effectiveness of such interventions.